Walking path-planning method for multiple radiation areas. (August 2016) - Liu, Yong-kuo; Li, Meng-kun; Peng, Min-jun; Xie, Chun-li; Yuan, Cheng-qian; Wang, Shuang-yu; Chao, Nan
Highlights: Radiation environment modeling method is designed. Path-evaluating method and segmented path-planning method are proposed. Path-planning simulation platform for radiation environment is built. The method avoids to be misled by minimum dose path in single area. Abstract: Based on minimum dose path-searching method, walking path-planning method for multiple radiation areas was designed to solve minimum dose path problem in single area and find minimum dose path in the whole space in this paper. Path-planning simulation platform was built using C# programming language and DirectX engine. The simulation platform was used in simulations dealing with virtual nuclear facilities. Simulation results indicated that the walking-path planning method is effective in providing safety for people walking in nuclear facilities.